Pengaruh Motif Hedonis & Religiusitas terhadap Pembelian Impulsif Online Generasi Senior Millennial melalui Mediasi Self Esteem - Veybitha, Yolanda; Pamuji, Muhni; Sakarina, Sari; Melvani, Frecilia Nanda (Forum Bisnis Kewirausahaan, 2025)
This study aims to measure the online impulsive buying behavior of the millennial senior generation (born in 1983-1990). This study uses a quantitative method with a survey method. A tool for measuring using SEM (Structural Equation Model) with LISREL software. The sample in this study was 470 respondents, they filled out a questionnaire online. The results of the study show that the effect of religiosity on impulsive buying is not significant. Furthermore, the calculation of the indirect effect of the religiosity variable through self-esteem mediation on impulsive buying shows a significant effect so that self-esteem in this study mediates perfectly (full mediated). But for the hedonic motive variable, self-esteem is only partially mediated. Further research has implications theoretically and practically. Keywords: Hedonic Motives, Religiosity, Self Esteem, Impulsive Buying